2020
DOI: 10.3390/nano10030530
|View full text |Cite
|
Sign up to set email alerts
|

Green and Economic Fabrication of Zinc Oxide (ZnO) Nanorods as a Broadband UV Blocker and Antimicrobial Agent

Abstract: Zinc oxide (ZnO) nanoparticles have gained widespread interest due to their unique properties, making them suitable for a range of applications. Several methods for their production are available, and of these, controlled synthesis techniques are particularly favourable. Large-scale culturing of Chlorella vulgaris produces secretory carbohydrates as a waste product, which have been shown to play an important role in directing the particle size and morphology of nanoparticles. In this investigation, ZnO nanorod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…The toxicity of ZnO-NPs can be attributed to the generation of reactive oxygen species (ROS), the release of Zn (Zn 2+ ) ions inside the microbes, and the change in cell wall permeability [ 63 ]. The generation of ROS is considered the major reason for nanotoxicity which involved the damage of cellular components (proteins, lipid, nucleic acid, phospholipid, amino acids) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of ZnO-NPs can be attributed to the generation of reactive oxygen species (ROS), the release of Zn (Zn 2+ ) ions inside the microbes, and the change in cell wall permeability [ 63 ]. The generation of ROS is considered the major reason for nanotoxicity which involved the damage of cellular components (proteins, lipid, nucleic acid, phospholipid, amino acids) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…These NPs were synthesized by the precipitation method using 2-mercaptoethanol as a capping agent. Tahizdeh et al [ 100 ] reported that ZnO nanorods at an MIC of 250 μg/mL had antimicrobial activity against E. coli , P. aeruginosa , S. aureus , and Enterococcus faecalis, excluding E. faecalis which was resistant to ZnO nanorods. These nanorods were small crystals 3.4 nm in size and the NPs were 150 nm in length and 21 nm in width (aspect ratio, 7.14).…”
Section: Antimicrobial Ctivity Against Pathogenic Microorganismsmentioning
confidence: 99%
“…fabricated the ZnO nanorods by controlled synthesis using secreted carbohydrates of Chlorella vulgaris . [ 105 ] In this study, the antibacterial ability of ZnO nanorods was also demonstrated.…”
Section: D Transition Metal–based Nanomaterials With Anisotropic Shape For Biomedical Applicationsmentioning
confidence: 72%